Prognostic value of miR-221 in human malignancy: evidence from 3041 subjects - Liu, Kangkang; Wang, Lining; Sun, Erlin (BMC cancer, 2019)
MiR-221, acting as onco-miR or oncosuppressor-miR, plays an important role in tumor progression; however, the prognostic value of miR-221 in human carcinomas is controversial and inconclusive. The objective of our study was to conducted a systematic review and meta-analysis of miR-221 in various types of human cancers. An online search of up-to-date electronic databases, including PubMed and Embase, was conducted to identify as many relevant papers as possible. 32 papers involving 3041 patients with different carcinomas were included in the analysis. Hazard ratios (HRs) of miR-221 were used to evaluate prognostic values. Thirty-two papers involving 15 cancers were included. MiR-221 was associated with a worse overall survival (OS) in patients, and a combined HR was 1.93 (95% CI of 1.43-2.60, 2080 patients, 22 studies, I-squared = 80.4%, P = 0.000); however, the combined HR for relapse-free survival (RFS) was 1.37 (95% CI of 0.75-2.48, 625 patients, 7 studies, I-squared = 78.8%, P = 0.000), and disease-free survival (DFS) was 1.24 (95% CI of 0.60-2.56, 539 patients, 5 studies, I-squared = 81.8%, P = 0.000). MiR-221 was shown to be associated with a poor OS in human carcinomas, and thus may serve as a useful predictor of clinical outcomes.